Diagnostic utility of bronchoalveolar lavage in children with complicated intrathoracic tuberculosis. Issue 7 (13th April 2021) - Goussard, Pierre; Croucamp, Roland; Bosch, Corne; Demers, Anne‐Marie; Morrison, Julie; Mfingwana, Lunga; Palmer, Megan; van der Zalm, Marieke M.; Friedrich, Sven O.; Janson, Jacques T.; Whitelaw, Andrew C.; Andronikou, Savvas; et al.
Abstract: Introduction: Bronchoscopy can be a useful tool in children with pulmonary tuberculosis (PTB) with severe disease potentially requiring intervention or in the face of diagnostic dilemmas. The aim of this study was to determine the value of Xpert MTB/RIF assay (Xpert) on bronchoalveolar lavage (BAL) samples in children with complicated PTB. Methods: Retrospective analysis of children with clinically diagnosed PTB, who underwent routine bronchoscopy over a 5‐year period at a large referral hospital. BAL and other respiratory samples were tested by microscopy, culture, and Xpert. We explored whether clinical, radiographic and bronchoscopy findings, and duration of antituberculosis treatment were associated with bacteriological confirmation. Results: One hundred and twelve out of one hundred and forty‐six (76.7%) children (median age 16 months) were on antituberculosis treatment for a median of 10 days at the time of bronchoscopy. Overall, bacteriological confirmation was achieved in 115 (78.7%), with 101 (69.2%) detected on BAL. Of those bacteriologically confirmed on BAL, 61.4% were positive by both Xpert and culture, 34.7% only by Xpert, and 3.9% only by culture. Sensitivity and specificity of Xpert compared with culture on BAL samples for children not on antituberculosis treatment were 94.1% (95% confidence interval [CI]: 71.3, 99.8) and 68.7% (95% CI: 41.3, 89.0), respectively. Conclusions: In children undergoing bronchoscopy for complicated PTB, Xpert testing of BAL had a high diagnostic yield in children already on antituberculosis treatment. Bronchoscopy should be considered if noninvasive respiratory specimens fail to confirm complicated TB.